Second Preparatory Meeting for the Xiv Ibero-American Judicial Summit Conclusions Cusco (09/28/2007) - Távara Córdova, Francisco (2007)
Presents the Federative Declaration of Brazil, in March 2008, under the thematic axis Modernization, Legal Security, Access and Social Cohesion: Justice Preparing for the Future